Studi Pengaruh Kendala Waktu Luang , Pengalaman Wisata, Citra Destinasi Dan Pengalaman Keluarga Terhadap Kunjungan Berulang - Najmi Pratama; Sujana Sujana (Jurnal Ilmiah Pariwisata Kesatuan, 2021)
The tourism sector is currently one of the important factors, because Indonesia's wealth and natural resources are the main factors in attracting tourists to destinations in Indonesia. Because of this attraction, Indonesia is attracted by local and foreign tourists. This makes the tourism industry entrepreneurs compete in presenting an attractive destination for tourists. Therefore a tourism industry must be able to determine which strategy is right in order to be able to compete. This research was conducted using SEM (Structural Equation Modeling) analysis on tourists to Bogor city destinations. The data used are the results of research questionnaires and the results of calculations using SPSS and LISREL data processing applications. In accordance with the identification of the problem above, the objectives of this study are (1) to determine the effect of free time constraints on repeated visits to Bogor city destinations. (2) determine the effect of tourist experience on repeated visits to tourist destinations in the city of Bogor. (3) determine the effect of destination image on repeated visits to Bogor city tourist destinations. (4) determine the effect of family experience on repeated visits to tourist destinations in the city of Bogor. The results showed (1) the free time constraint had a positive and significant impact on repeated visits because the t-value was 5.1 > CR value 1.96, so H1 was accepted and H0 was rejected. Which means that free time constraints have a positive and significant effect on repeat visits. (2) Travel experience has a positive and significant impact on repeat visits because the t-Value value is 2.08 > CR value 1.96 then H2 is accepted and H0 is rejected. Which means that the tourist experience has a positive and significant effect on repeat visits. (3) Destination image has a positive and significant impact on repeat visits because the t-value is 2.66 > CR value 1.96, so H3 is accepted and H0 is rejected. Which means that the image of the destination has a positive and significant effect on repeat visits. (4) Family Experience has a positive and significant impact on repeat visits because the t-Value is 2.09 > CR value of 1.96, so H4 is accepted and H0 is rejected. Which means that family experience has a positive and significant effect on repeat visits. Keywords : Effect of leisure time constraints, travel experience, destination image and Family Experience of Repeat Visits